2022
DOI: 10.1177/12034754221116115
|View full text |Cite
|
Sign up to set email alerts
|

Practical Guidelines for Managing Patients With Hidradenitis Suppurativa: An Update

Abstract: Hidradenitis suppurativa (HS) is a chronic, inflammatory skin disease that is characterized by the formation of comedones, papules, nodules, abscesses and sinus tracts in the axillary, inframammary, groin, and gluteal areas. Up to 3.8% of the Canadian population has HS, though due to a lack of awareness of HS, many patients are initially misdiagnosed and do not receive adequate treatment early on in the disease course. Once a diagnosis of HS is made, developing an effective management plan can be a dilemma for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 255 publications
0
5
0
Order By: Relevance
“…It is recommended only for acute abscesses for pain relief ( 42 ). For extensive Hurley Stage III HS, wide local surgery or carbon dioxide laser excision may be necessary to achieve disease control ( 44 ). …”
Section: How Is Hs Treated and What Can The Gp Do?mentioning
confidence: 99%
See 1 more Smart Citation
“…It is recommended only for acute abscesses for pain relief ( 42 ). For extensive Hurley Stage III HS, wide local surgery or carbon dioxide laser excision may be necessary to achieve disease control ( 44 ). …”
Section: How Is Hs Treated and What Can The Gp Do?mentioning
confidence: 99%
“…For extensive Hurley Stage III HS, wide local surgery or carbon dioxide laser excision may be necessary to achieve disease control ( 44 ).…”
Section: How Is Hs Treated and What Can The Gp Do?mentioning
confidence: 99%
“…Similarly, this may substantiate the lack of effective therapies for HS disease control as indicated by recent guidelines. 3 Preliminary clinical trial results evaluating povorcitinib and upadacitinib use demonstrated 45.9% and 38.3% of patients achieving HiSCR50 respectively. 4,5 These findings are in keeping with our review.…”
mentioning
confidence: 99%
“…Current challenges in the management of HS were consistent irrespective of HS patient load, with the greatest knowledge gaps related to surgical management, pharmacologic and non-pharmacologic strategies, and practical aspects of care. There is an appetite for learning about evolving HS management strategies and with new treatments on the horizon and recently published practical guidelines, 5 we are hopeful that dermatologists’ knowledge base will increase. There is also an opportunity for raising awareness about HS and for collaborations between dermatologists, rheumatologists, surgeons, urgent care clinics, general practitioners, industry partners, and HS patient organizations to develop resources to support improved patient outcomes and satisfaction.…”
mentioning
confidence: 99%
“…1 Indeed, there is growing excitement for new targeted agents 2 to treat HS that are in late phases of clinical development and regulatory submission. Although a multidisciplinary approach is recommended, [3][4][5] dermatologists are often the quarterbacks for managing this complex disease. The last targeted HS biologic treatment to be approved in Canada was Humira (adalimumab) more than 7 years ago.…”
mentioning
confidence: 99%